A safe space for healing: boundaries, power and vulnerability in pastoral care - Berry, Jan (Theology & sexuality, 2014)
This article is a theological reflection on issues of power and vulnerability in relation to pastoral boundaries. It starts with a reflection on my experience in training ordinands and pastoral carers, and an awareness that mandatory training in safeguarding often seems to focus on regulations and procedures, rather than power dynamics and self-awareness. The article goes on to summarize recent literature relating to pastoral boundaries, before exploring the underlying concepts of power and vulnerability, using theologians such as Moltmann and Bonhoeffer on the vulnerability of God, and the feminist writings of Carter Heyward and Mary Grey on mutuality. It concludes by arguing that boundaries provide a safe space for the delicate balancing of vulnerability, risk and power in the pastoral relationship.